Systematics studies of three Aquailaria species - Nur Qistina, binti Othman (Universiti Malaysia Sarawak (UNIMAS), 2012)
A systematic study of Aquilaria beccariana Tiegh., Aquilaria malaccensis Lam. and Aquilaria microcarpa Baill. based on morphology and molecular characteristics were conducted. They are important species for producing the aromatic resin known as gaharu which fetches high market value and have been listed in Appendix II of CITES (Convention of International Endangered Species). The herbarium specimens were used for the morphological study while fresh samples of the seedlings grown in the green house at Universiti Malaysia Sarawak and collection from the field were used for the molecular study. The objectives of this study were to document the morphological characteristics and to develop species-specific DNA markers for these three species to be used as a tool to identify and differentiate the species. This study described in detail the vegetative, floral, and fruits macro and micromorphology to provide detail taxonomic information for easy identification of the species. Two molecular techniques were chosen, the RAPD (Random Amplified Polymorphic Deoxyribonucleic Acid) fingerprinting and RAPD-SCAR (SequenceCharacterized Amplification Region). Based on the RAPD fingerprinting, the genetic profiles were obtained for A. beccariana and A. microcarpa generated using universal primers M 13 and OPA 10 but for A. malaccensis the profile was generated only through primer OPA 10. The amplicons obtained were subjected to RAPD-SCAR technique and successfully obtained the species specific DNA marker. Two primer pairs were developed and designated for each A. beccariana and A. microcarpa based on primer M 13 and OPA 10 while only one primer pair was designated for A. malaccensis based on primer OPA 10. All five primer pairs were considered novel findings. All morphology and molecular information obtained in this study would be most useful especially in resolving the difficulty in differentiating between species and important knowledge in implementing any conservation purposes and selection of seedlings for commercial plantation.